The Estimation of Carbon Stock Potential on Merkus Pine (Pinus merkusii Jungh. et de Vriese) in KPH Cianjur, Perum Perhutani III West Java and Banten - Bambang Hero Saharjo; Hadi Firdaus Prima Wardhana (Jurnal Silvikultur Tropika, 2011)
Global warming is one of the major environmental issues that currently concern to the various parties. Because of global warming, increasing in average temperature of earth's sea and land caused by industrial activity and reduction of forest cover due to deforestation, especially lately. Based on these evolving issues and considering the importance of the role of forests in absorbing carbon from the air and store it in forest biomass, it is necessary a lot of research that could encourage the continued development of carbon in biomass. One important aspect of research is to know the potential of carbon stored in the stands of pine.